(untitled) (ICADE. Revista de la Facultad de Derecho, 2015)
Autores: Marta Gisbert Pomata, Sara Díez Riaza, Cristina Carretero González y Verónica González-Choren Respaldiza. Editorial: Civitas. Año de publicación: 2013, 688 pág. ISBN: 978-84-470-4567-9